Feasibility and complications of videocapsule endoscopy in dogs weighing 7 kg or less - Camille St‐Jean; Allison Collier; Alex Zur Linden; Alexa Bersenas; Alice Defarges (Journal of Veterinary Internal Medicine)
Abstract Background Videocapsule endoscopy (VCE) is a valuable tool for investigating gastrointestinal (GI) diseases in dogs. Its use is not recommended in dogs ≤4.3 kg, because of risks of GI endoscopic capsule (EC) retention and bowel obstruction. Objectives Describe the feasibility and complications of VCE in dogs ≤7 kg. Animals Twenty‐six client‐owned dogs. Methods Retrospective study describing the signalment, previous GI imaging, indications, findings, and complications of canine VCE studies submitted to Infiniti Medical between March 2020 and January 2023. Results The median weight and age of dogs was 5.6 kg (range, 3‐7) and 8.8 years (range, 1‐16), respectively. Two capsules were administered endoscopically into the duodenum (1) and stomach (1). Sixteen out of 26 (62%, 95% CI, 40.51‐79.70) dogs that underwent VCE had incomplete studies. Of the 24 capsules administered per os, 15 led to incomplete studies (battery died in the stomach (14), EC was vomited (1)). Body weight <5 kg significantly increased the risk of an incomplete study (OR: 3.67, 95% CI, 1.56‐inf, P = .0074). Median esophageal, gastric, and small bowel transit time were 5 seconds (range, 1‐180), 240 minutes (range, 17‐335), and 73.5 minutes (range, 5‐168), respectively. All 10 dogs with overt GI bleeding had a possible origin identified with VCE. Complications were limited to vomiting (1/26, 3.85%, 95% CI, 0‐11.20). Conclusions and Clinical Importance Videocapsule endoscopy is a safe and informative procedure even when performed in dogs as small as 3 kg. However, weighing <5 kg increases the risk of incomplete studies.